Carrot and Shrimp Head Flour as Feed Substitute for Comet Fish (Carassius auratus) Color - Zhalifunnas, Muhammad Ariq; Rahim, Andi Rahmad; Aminin, Aminin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Comet fish (Carassius auratus) are one of the popular ornamental fish due to their beautiful colors and body shapes. The enhancement of comet fish colors is often done by adding feed ingredients that contain carotenoids, such as carrot powder and shrimp head powder. This study aims to analyze the effect of adding carrot powder and shrimp head powder on growth rate, survival rate, feed conversion ratio, feed utilization efficiency, and the coloration of comet fish. The study was conducted using four different feed treatments: (A) 50% commercial pellets + 50% carrot powder, (B) 50% commercial pellets + 50% shrimp head powder, (C) 50% commercial pellets + 25% carrot powder + 25% shrimp head powder, and (K) 100% commercial pellets (control). Each treatment was replicated three times, and observations were made over 40 days. The results showed that the addition of carrot powder and shrimp head powder did not significantly affect daily growth rate and feed utilization efficiency. However, there was a significant effect on absolute length growth, with treatment A providing the best results. The survival rate of comet fish was also not significantly affected by feed treatments. Color analysis indicated that the combination of carrot powder and shrimp head powder (treatment C) provided the best yellow color intensity. The addition of carrot powder and shrimp head powder in the feed can enhance the color intensity of comet fish, especially the yellow color. However, this treatment did not significantly affect daily growth rate and feed utilization efficiency. This study provides important information for ornamental fish breeders in improving the color quality of comet fish through natural feed.